Renewing first year curricula for social sciences and humanities in the context of discipline threshold standards : final report. - Thomas, Theda; Allen, Pamela; Wallace, Joy; Jones, Adrian; Cole, Bronwyn; Sheridan Burns, Lynette; Lawrence, Jill; Clark, Jennifer (Office for Learning and Teaching, 2015)
Curriculum renewal in the social sciences and humanities is needed to ensure that the sector is able to meet the discipline threshold standards that TEQSA will specify. This is the final report from a project that focused on the first year for key disciplines in the social sciences and humanities and asked the question: what are the skills and capabilities that we need to develop in our first year students so that, in their final year, they can meet discipline threshold and AQF standards? To determine the answer to this question, the project worked within active national networks to use a collegial approach that engaged students and lecturers teaching in different disciplines in the first year across multiple universities. The project also collected a set of resources that provide ideas for good practice in assessment and other activities that might be used to develop and measure those skills for dissemination nationally and internationally.